Acute mitragynine administration suppresses cortical oscillatory power and systems theta coherence in rats. (July 2020) - Thériault, Rachel-Karson; Manduca, Joshua D; Blight, Colin R; Khokhar, Jibran Y; Akhtar, Tariq A; Perreault, Melissa L
Background: Mitragynine is the major alkaloid of Mitragyna speciosa (kratom) with potential as a therapeutic in pain management and in depression. There has been debate over the potential side effects of the drug including addiction risk and cognitive decline. Aims: To evaluate the effects of mitragynine on neurophysiological systems function in the prefrontal cortex (PFC), cingulate cortex (Cg), orbitofrontal cortex, nucleus accumbens (NAc), hippocampus (HIP), thalamus (THAL), basolateral amygdala (BLA) and ventral tegmental area of rats. Methods: Local field potential recordings were taken from animals at baseline and for 45 min following mitragynine administration (10 mg/kg, intraperitoneally). Drug-induced changes in spectral power and coherence between regions at specific frequencies were evaluated. Mitragynine-induced changes in c-fos expression were also analyzed. Results: Mitragynine increased delta power and reduced theta power in all three cortical regions that were accompanied by increased c-fos expression. A transient suppression of gamma power in PFC and Cg was also evident. There were no effects of mitragynine on spectral power in any of the other regions. Mitragynine induced a widespread reduction in theta coherence (7–9 Hz) that involved disruptions in cortical and NAc connectivity with the BLA, HIP and THAL. Conclusions: These findings show that mitragynine induces frequency-specific changes in cortical neural oscillatory activity that could potentially impact cognitive functioning. However, the absence of drug effects within regions of the mesolimbic pathway may suggest either a lack of addiction potential, or an underlying mechanism of addiction that is distinct from other opioid analgesic agents.